Dynamic responses of offshore wind turbine considering soil nonlinearity and wind-wave load combinations. (1st December 2020) - Cao, Guangwei; Chen, Zhixiong; Wang, Chenglong; Ding, Xuanming
Abstract: The existing p - y method that is capable of considering soil-structure interaction (SSI) might not be appropriate for large diameter piles widely used in offshore wind turbine structures. In addition, a simplified way is often adopted for the dynamic analysis of OWT, which simplifies or ignore the SSI, blades, ocean environmental loads and operational conditions. Considering these, a new finite element model (FEM) is described for monopile-supported offshore wind turbines, including components of soil reactions, wind and wave combinations, monopile-tower-blades system. This model allows us to simulate the interaction between the large diameter pile and its surrounding soil and reveals more real dynamic responses of OWT under stochastic ocean environmental loads. This paper discusses the difference of the dynamic responses between the OWT model with traditional p-y method and the new model, the numerical analysis shows that traditional p-y method overestimates the top displacements of OWT under stochastic wind and wave loads. Based on the proposed model, the effects of wind-wave combination, wind-wave misalignment angle and operational conditions on the structural responses are further investigated. The combination of 90° wind-wave angle and operating condition is found to be the most unfavorable situation. Highlights: A new FE model is described for OWT, and can reveal more real dynamic responses of OWT supported by large diameter pile. Compared with a new model, the traditional  p-y  method will overestimate top displacements of OWT under wind and wave loads. The combination of the 90°wind-wave angle and operating condition should be considered for a safer design of OWT.